(untitled) (The Pakistan Development Review, 2012)
Dividend behaviour has extensively been reviewed by many researchers from time to time across different countries. Empirical evidences observed in most of the studies reveal equivocal results about dividend theories [Bhattacharyya (2007)]. Since, in absence of any unanimous findings, need for future research has not been restricted, theoretically. In developing countries like Pakistan, where limited research is available on corporate dividend policy, need for future research is more looked for. Most of the available research papers, address only firm specific determinants of dividend policy. Do macroeconomic variables influence corporate financing decisions? The need to address this question is the prime motive of this research paper. Major objective of this paper is to observe dividend behaviour of listed firms in Pakistan under monetary policy restrictions and this is the first attempt of its kind in Pakistan to the best of my Knowledge. This study is very relevant in present scenario since State Bank of Pakistan (SBP) has been persistently pursuing restricted monetary policy since 2005 to control inflation.